Safety, tolerability and immunogenicity of GS-4774, a hepatitis B virus-specific therapeutic vaccine, in healthy subjects: A randomized study - Gaggar, Anuj; Coeshott, Claire; Apelian, David; Rodell, Timothy; Armstrong, Brian R.; Shen, Gong; Subramanian, G. Mani; McHutchison, John G. (Vaccine, 2014)
•GS-4774 is being developed as a therapeutic vaccine for chronic HBV infection.•GS-4774 consists of yeast cells that express well-conserved regions of HBV proteins.•GS-4774 was safe and well-tolerated in healthy subjects at all doses evaluated.•GS-4774 led to HBV-specific immune responses after weekly and monthly immunization.•GS-4774 is being tested in patients with chronic HBV infection. GS-4774 is a recombinant, heat-killed, yeast-based immunotherapy engineered to express hepatitis B virus (HBV)-specific antigens. GS-4774 is being developed as a therapeutic vaccine for chronic HBV infection. The aim of this study was to assess the safety, tolerability and immunogenicity of GS-4774 in healthy subjects. This was a randomized, open-label, dose-ascending study. Subjects were allocated to one of three dose groups (n=20 per group) to receive 10, 40 or 80 yeast units (YU; 1YU=107 yeast) of GS-4774 in two immunization regimens (five subcutaneous injections at weekly intervals with one monthly booster or three subcutaneous injections at monthly intervals). T-cell-mediated responses were determined by interferon (IFN)-γ enzyme-linked immunospot (ELISpot) assay and lymphocyte-proliferation assay (LPA). Adverse events were reported by 39 of 60 (65%) subjects; all were mild or moderate and none was serious. Adverse events occurred most frequently in the highest dose group, 80YU, and the number of individual events was higher after weekly immunization than monthly. The most common adverse events were injection-site reactions. Most (88%) subjects responded to GS-4774 by at least one of the T-cell assays. Following immunization with GS-4774, IFN-γ-producing T-cells specific for HBV antigens were detectable in 30 (51%) subjects. The ELISpot response was observed at all doses, with the highest frequency of responders occurring at the highest dose (10YU: 45%; 40YU: 35%; 80YU: 74%). Proliferative responses to HBV recombinant antigens were observed in 90% subjects; responses were mainly independent of GS-4774 dose and immunization regimen. GS-4774 was safe and well-tolerated in healthy subjects with injection-site reactions being the most frequently reported adverse events. With both weekly and monthly regimens, GS-4774 provided HBV-specific immune responses at all doses evaluated. Further evaluation of GS-4774 is ongoing in patients with chronic HBV infection. Clinical trial registry: Clinicaltrials.gov (NCT01779505)